v-5/3-v=-3(v-1)

Simple and best practice solution for v-5/3-v=-3(v-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v-5/3-v=-3(v-1) equation:


v-5/3-v=-3(v-1)

We simplify the equation to the form, which is simple to understand
v-5/3-v=-3(v-1)

Simplifying:
v-1.66666666667-v=-3*(v-1)

Reorder the terms in parentheses
v-1.66666666667-v=+(-3v+3)

Remove unnecessary parentheses
+v-1.66666666667-v=-3v+3

We move all terms containing v to the left and all other terms to the right.
+1v-1v+3v=+3+1.66666666667

We simplify left and right side of the equation.
+3v=+4.66666666667

We divide both sides of the equation by 3 to get v.
v=1.55555555556

See similar equations:

| 8n-(6n+5)=7 | | 190-2x+x+10=180 | | 2x-1=y | | 2x+10=y | | 4+4x/3=6 | | 2x-13=y | | -3x+5=y | | 3x+6=33 | | 13=-3x-8 | | (3x-1)(x+4)= | | 2y-6y+8=2(-2y+9) | | 10x^2-20=-5x | | 4x+9-y= | | 10(y-3)=5(y+5) | | x^2-10x-25=36 | | 12x^2+18=30+12x | | 4x^2-40[x]+51=0 | | x^2-10x-25=6 | | x-10x-25=6 | | e(n)=2(n) | | (y-5)(5+5)= | | 8+3(6+4)= | | .5(6x+4)=x+2(x+1) | | 3(7x-2)+5=26 | | 15=3n+6p | | -4w+8=2w+44 | | x=5+4y | | 4x=7x-2 | | (7p+8)+(2p-3)= | | 2x-3=9-x | | 4544=71a | | -4x-4=-8 |

Equations solver categories